Inductors in LTCC utilizing full tape thickness features - Boutz, Adam (Kansas State University, 2009)
Inductors have been produced in LTCC in a unique manner that increases the cross-sectional area of the conductor. The method uses metal-filled trenches and cavities in the tape to create conductors which are as thick as an entire layer of tape. This geometry helps to compensate for high-frequency non-idealities such as skin effect, current crowding, and proximity effect. An array of test structures has been fabricated. The measured results achieved inductors with Qs of 60 and suggest that Qs up to 100 are possible. Accurate measurements of such values require careful consideration of error sources and are discussed. A potential application of the inductors is presented in a two-pole filter, which has been modeled and fabricated. Lastly, a list of conclusions which would be helpful for future work on this subject is presented.
Keywords: LTCC; Inductors; High-Q; FTTF; Engineering, Electronics and Electrical (0544)